Analisis finansial usaha ternak ayam ras petelur (studi kasus CV Muara Puncak di Desa Muara Putih Kecamatan Natar) - Ilyas Wiguna, Ahmad; Eka Wati, Novi; Herdiansyah, Riko (Fakultas Peternakan Universitas Tulang Bawang, 2023)
The purpose of this research is to analyze financially and analyze the feasibility of laying hens CV. Puncak Estuary. The research was conducted in October - December 2022. Located in Muara Putih Village, Natar District, South Lampung Regency. The research method used in this study is a case study. The type of data used is descriptive, quantitative and qualitative. The data sources used are primary data and secondary data. Case studies are used with descriptive analysis with a quantitative approach, namely presenting a summary of data or values ​​calculated based on available data or data collected. The results of the research show that the financial analysis is Net Present Value (NPV) > 0, Revenue Cost Ratio (RCR) > 1, Internal Rate of Return (IRR) > cost of capital, Break Event Point (BEP) has been fulfilled, Return On Investment (ROI) ≥ 10%, and Payback Period (PP) < business year that has been run.